2021
DOI: 10.21037/apm-21-485
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of delivery methods on postpartum pelvic floor function in primiparas: a retrospective study

Abstract: Background: The present study sought to investigate the short-term effects of different delivery methods on postpartum pelvic floor function in Chinese primiparas. Methods: Primiparous women who delivered a full-term, cephalic, singleton infant at our hospital between January 1, 2018 and August 15, 2019 were recruited into this study. All women underwent pelvic floor function screening at 6-8 weeks postpartum. Tests included postpartum Pelvic Organ Prolapse Quantification (POP-Q) score, incidence of urinary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…So far it can be observed that cesarean delivery may cause UI due to the fact that the bladder is usually detached from the uterus to allow access to the anterior segment (13) and during vaginal delivery lacerations of the anal sphincter may occur and episiotomy increased the risk of lesions of the pelvic floor muscles increasing the risk of UTI. (14) The limitations found were that there was little research done on the specific reason that causes POP (apical, posterior) in cesarean sections. Thus, for future studies, it is suggested to find the exact cause of apical and posterior POPs in cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…So far it can be observed that cesarean delivery may cause UI due to the fact that the bladder is usually detached from the uterus to allow access to the anterior segment (13) and during vaginal delivery lacerations of the anal sphincter may occur and episiotomy increased the risk of lesions of the pelvic floor muscles increasing the risk of UTI. (14) The limitations found were that there was little research done on the specific reason that causes POP (apical, posterior) in cesarean sections. Thus, for future studies, it is suggested to find the exact cause of apical and posterior POPs in cesarean section.…”
Section: Discussionmentioning
confidence: 99%